Ketangguhan Mental Atlet Menjelang Pertandingan pada Tahap Persiapan Khusus Melalui Metode Pelatihan Mental Systematic Literature Review - Nurfauziyah, Dea Meisya; Hambali, Burhan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to determine the level of mental toughness of athletes before a match during the special preparation stage through mental training methods. The method used in this research employs the SLR (Systematic Literature Review) method, with literature searches conducted using digital databases (Google Scholar, Publish or Perish, Scopus, and others). This research was conducted based on three keywords: mental toughness, mental training, and training periodization. Conclusion: There is an increase in mental toughness leading up to the competition in the specific phase through mental training with various methods that are tailored to the needs and proportions of the athletes themselves. Keywords: mental toughness, mental training, training periodization